Optimal Thermal Output of an Absorption Heat Pump with Steam Heating Integrated in a PT-60/70-130/13 Steam Turbine - Oleksandr L. Shubenko; Viktoriia O. Tarasova; Mykola Yu. Babak; Oleksii Yu. Boiarshynov (Journal of Mechanical Engineering)
The problem of determining the optimal thermal power of the absorption bromide-lithium heat pump (AHP) with steam heating, integrated into the thermal scheme of the PT-60/70-130/13 steam turbine when operating in the mode with a slight opening of the rotary regulating diaphragm, was formulated and solved. The turbine plant released steam to consumers and provided heat according to the schedule of 150 / 70 ºС. The characteristics of AHP were modeled using approximate dependencies based on the characteristics of thermotransformer manufacturers. AHP was heated by steam from the production selection of the turbine after the steam screw machine installed for energy saving. The general optimization problem with the objective function of total changing the monthly fuel consumption after the integration of AHP, based on the average monthly outdoor air temperature in the heating season in Ukraine, was divided into 6 auxiliary optimization problems. The control parameters of these problems were: thermal capacity of the AHP, steam pressure in the turbine condenser and at the inlet to the heat pump, steam pressure in the turbine headю These problems were solved by the coordinate descent method. Modes with steam consumption in the production selection of the turbine for the consumers were studied: 15, 30 and 45 t/h (with parameters: 1.296 MPa, 280 ºС) and mains water: 1600, 1650 and 1700 m3/h. Their feature is the provision of "useful" generation in volumes corresponding to the work of PT-60/70-130/13 without AHP with a closed rotary diaphragm. For all considered options of the turbine load, the optimal power of the integrated AHP is defined as 20 MW. During the heating period PT-60/70-130/13 with AHP 20 MW when operating in a mode close to the thermal load with the lower of the studied consumptions of production steam and mains water leads to savings of: fuel by ~3.5%, softened water by 8.5%, technical of water by 79.9%, as well as to a noticeable ecological effect due to the reduction of harmful emissions into the atmosphere. The preliminary payback period of AHP is close to 3 years. It is noted that the option of the integrated turbine with a partially open regulating diaphragm at the accepted prices for fuel and electricity loses in terms of economic indicators to the option with a closed diaphragm.